Stereotype Representation of Healthy Skin of East Asian Women in Somethinc Skincare Advertisements - Retno Adrin Pramesti; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2025)
This study analyzes the influence of the representation of the stereotype of healthy skin of East Asian women in Somethinc advertisements on beauty perception in Indonesia. Using Roland Barthes' semiotic approach, this research explores the visual signs in the advertisements to uncover how media reinforces global beauty standards that affect Indonesian women. The findings show that the use of a South Korean brand ambassador in the ad introduces and strengthens the beauty stereotype that women must have bright, smooth, and healthy skin. This creates pressure on Indonesian women, particularly younger generations, to meet these beauty standards, which can potentially harm their self-confidence and cause anxiety about their physical appearance. This study aims to provide insights for the beauty industry to become more sensitive to the diversity of beauty concepts and their social impact, as well as encourage more inclusive representation.